Learn Adobe Illustrator CC for graphic design and illustration : Adobe Certified Associate exam preparation - Chelius, Chad; Schwartz, Rob, 1969- (Adobe Press : Pearson Education, 2019)
Adobe Illustrator CC is the most popular vector illustration application available. Print and screen designers use it to create powerful artwork composed of shapes, color, and highly styled text. Illustrator is a necessary tool for anyone considering a career in the visual design or illustration field. Learn Adobe Illustrator CC by building cool creative projects that teach you how to: Design and illustrate a promotional postcard Style text to create a logotype for a business Combine illustrations and text to create infographics Trace a photograph to use in an eye-catching concert poster Design icons and graphics for a mobile device interface This study guide uses video integrated with text to help you gain real-world skills that will get you started in your career in graphic design using Adobe Illustrator CC 2018 and lays the foundation for taking the Adobe Certified Associate (ACA) certification exam in that field. A mix of 6 project-based lessons, 8 hours of practical videos, and interactive quizzes prepares you for an entry-level position in a competitive job market. Purchasing this book gives you access to valuable online extras. Follow the instructions in the book's "Getting Started" section to unlock access to: Web Edition containing instructional video embedded in the complete text of the book with interactive review questions along with product updates Downloadable lesson files you need to work through the projects in the book